The Effect of Internal and External Factors on the Proportion of MSME Sector Financing in Sharia Business Units in Indonesia - Rahmawati, Siti; Fitri, Resfa; Alim, Ahmad Syahirul; Irfany, Mohammad Iqbal (Review on Islamic Accounting, 2025)
This paper aims to analyze the response of the proportion of MSME financing in Sharia Business Units in Indonesia to internal and external factor shocks. Additionally, it seeks to determine the contribution of each factor to the diversity of MSME financing proportions. This study employs the Vector Error Correction Model (VECM). The Covid-19 pandemic is included as an exogenous dummy variable. The analysis uses monthly data from January 2019 to December 2024, sourced from the Sharia Banking Statistics published by the Financial Services Authority (OJK). The study found that Third Party Funds, Operational Expenses to Operational Income, and the BI rate have a positive impact on MSME financing proportions in UUS. Conversely, Non Performing Financing (NPF), Return on Assets (ROA), Gross Domestic Product (GDP), Bank Indonesia Sharia Certificate (SBIS) exhibit a negative impact. The MSME financing proportion itself is the most dominant factor in financing variability, followed by NPF, BOPO, GDP, BI rate, SBIS, ROA, and DPK. This finding represents the supply side, referring to banks as financing providers. To obtain a more comprehensive perspective, further analysis is needed from the demand side by considering the characteristics of MSMEs as financing recipients. This area of research remains relatively underexplored, which is mandated to allocate at least 30% of its financing to the MSME sector, although actual disbursement remains around 10%.